A major antigenic domain of hantaviruses is located on the aminoproximal site of the viral nucleocapsid protein - Gött, Peter; Zöller, Lothar; Darai, Gholamreza; Bautz, Ekkehard K. F. (Virus genes, 1997)
Hantavirus nucleocapsid protein has recently been shown to be an immunodominant antigen in hemorrhagic with renal syndrome (HFRS) inducing an early and long-lasting immune response. Recombinant proteins representing various regions of the nucleocapsid proteins as well as segments of the G1 and the G2 glycoproteins of hantavirus strains CG18-20 (Puumala serotype) and Hantaan 76-118 have been expressed in E. coli. The antigenicity of these proteins was tested in enzyme immunoassays and immunoblots. These studies revealed that human IgG immune response is primarily directed against epitopes located within the amino acid residues 1 to 119 of the amino terminus of viral nucleocapsid proteins. This fragment was recognized by all HFRS patient sera tested (n=128). The corresponding enzyme immunoassays proved to be more sensitive than the indirect immunofluorescence assays. Furthermore, the majority of bank vole monoclonal antibodies raised against Puumala virus reacted specifically with this site. A recombinant G1 protein (aa 59 to 401) derived from the CG 18-20 strain was recognized by 19 out of 20 sera from HFRS patients.